How Safe is Organic Cassava? - Seena Radhakrishnan, AR; Suja, G (JOURNAL OF ROOT CROPS, 2017)
The concern for food safety, environmental issues and human health has stimulated interest in alternative agricultural systems like organic farming. Cassava (Manihot esculenta Crantz) is an important tropical tuber crop that plays a significant role in the food and nutritional security in rural livelihoods. Since the information on the quality of organically grown cassava tubers is meagre, a field experiment was conducted in split plot design over a period of three years at ICAR-Central Tuber Crops Research Institute, Thiruvananthapuram, Kerala, India. The aim was to compare the tuber quality by evaluating the biochemical and mineral contents of tubers of three varieties of cassava, H-165, Sree Vijaya and Vellayani Hraswa grown under various production systems, viz., traditional, conventional, integrated and two types of organic (with or without biofertilizers). The varieties were assigned to main plots and production systems to subplots. Organic farming improved biochemical parameters by lowering the cyanogenic glucoside content (-19.60%), enhancing dry matter (+2.72%), starch (+ 8.60%), crude protein (+7.72%), sugar (+54.62%), ash (+38.42%) and fibre (+20.56%) contents. Besides, the mineral contents like P, K, Ca, Mg, Fe, Mn and Zn status of the tubers were enhanced by 1.25, 10.13, 12.89, 40.79, 59.03, 6.92 and 27.40% respectively over conventional practice in the current research. Thus, organic management in cassava produced quality and safe tubers.